A Literature Review on Using the First Language (L1) in the EFL Classroom - Suantara, I Wayan Ardhi (The Art of Teaching English as a Foreign Language (TATEFL), 2023)
Among foreign students themselves, the usage of L1 (first language) in the EFL classroom has long drawn attention. It was seen as a challenge to teach the TL without utilizing L1, as it was frequently used in the learning technique to teach other languages. This paper analyzed and emphasized the usage of L1 in classroom instruction in EFL. The literature study was conducted using a review and analysis of around 7 relevant journal publications. The outcome demonstrated how using L1 in the EFL classroom helped to foster a good learning environment. It indicates that students' views regarding the usage of L1 in the EFL classroom were good, as seen by their willingness such as in receiving instructions, understanding difficult topics, learning new vocabularies, and socializing in the classroom. The study result recommends looking into the effect of the use of L1 in the EFL classroom.